Pembuatan Program Aplikasi Inventori pada PD. Duta Bangunan - Mico Junianto; Desi Arisandi; Zyad Rusdi (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
The aim of this thesis is to assist the process of listing and checking items as well as facilitating the transaction process in PD. Duta Bangunan storehouse. The Method used in developing this application program is SDLC (System Development Life Cycle). This application is desktop based that holds informations regarding PD. Duta Bangunan's inventory system. The use of this application is to supervise the product acquisition in PD. Duta Bangunan's storehouse. In addition to supervising the items, this application could generate reports with computerized one. Those reports are; report of incoming items, report of the items out, also report of return items from suppliers. This application was designed with Visual Studio 2012, using SQL Server Management Studio 2012 as the database system, Crystal Reports is also used to generate the reports.From the testing phase, the results gave conclusion that is the system created above is able to be used, and could help PD. Duta Bangunan with monitoring their inventory